Giant cell tumor of tendon sheath: a case series - Korumilli, Ramesh Kumar; Srikanth, Jakkula; Muvva, Sri Harsha; Reddy, B. M. Yashwanth (International Surgery Journal, 2018)
Giant cell tumor of tendon sheath is a relatively rare non-malignant soft tissue tumor arising from the synovial cells and is associated with high recurrence rate. Many factors are considered for high recurrence including proximity to distal interphalangeal joints, presence of degenerative joint disease, pressure erosions in the radiograph and increased mitotic activity. But the most common cause for recurrence is incomplete surgical excision. However, it is the second most common tumor in hands after ganglion cysts. Here we present a case series comprising of 3 cases for whom marginal excision was done and they were kept on regular follow up without any recurrence.